Neonatal Outcomes of Term Infants Born with Meconium-Stained Amniotic Fluid - Carlo Dani; Martina Ciarcià; Vittoria Barone; Mariarosaria Di Tommaso; Federico Mecacci; Lucia Pasquini; Simone Pratesi (Children, 2023)
Background Meconium-stained amniotic fluid (MSAF) is considered an alarming sign of possible fetal compromise and it has recently been reported that neonatal outcome correlates with the degree of meconium thickness. Methods We retrospectively studied 400 term infants allocated in clear amniotic fluid and grade 1, 2, and 3 MSAF groups on the basis of color and thickness of AF. Multivariable logistic regression analysis was performed to evaluate the potential independent effect of delivery with MSAF of different severity on the risk of a composite adverse neonatal outcome. Results We found that delivery with grade 2 (OR 16.82, 95% Cl 2.12–33.52; p = 0.008) and 3 (OR 33.79, 95% Cl 4.24–69.33; p < 0.001) MSAF is independently correlated with the risk of adverse neonatal outcome, such as the occurrence of at least one of the following: need of resuscitation in the delivery room, blood cord pH < 7.100, occurrence of meconium aspiration syndrome (MAS), persistent pulmonary hypertension (PPH), transient tachypnea of the newborn (TTN), acute respiratory distress syndrome (ARDS), hypoxic-ischemic encephalopathy (HIE), and sepsis. Conclusions There is a positive correlation between the severity of amniotic fluid meconium staining and thickness and the outcomes of term infants. Therefore, the evaluation and grading of MSAF during labor is useful in order to plan for the presence of a neonatologist at delivery for immediate and proper neonatal care.